Penegakan Hukum terhadap Parkir Liar di Kota Surakarta - Ilham Hendra Prabowo; Widi Nugrahaningsih; Aryono Aryono (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Parking is a public service with the potential to generate revenue for local governments if managed officially and transparently. Law No. 1 of 2022 on Financial Relations between the Central and Regional Governments states that parking taxes and fees are important components of regional income. In Surakarta, parking management is regulated by Mayor Regulation No. 5 of 2024 concerning Procedures for Collecting Parking Fees. However, the rise of illegal parking practices causes revenue leakage, as unofficial parking operations do not contribute through taxes or levies.This study aims to examine law enforcement efforts against illegal parking in Surakarta and its economic impact on local communities. Using an empirical legal research method, the study explores actual behaviors and verbal patterns in the field.Findings reveal that the Department of Transportation and law enforcement authorities in Surakarta adopt both preventive and repressive approaches to tackle illegal parking, aiming to restore order and reduce public losses. These enforcement efforts significantly affect the local economy by increasing regional revenue and fostering a more orderly and business-friendly environment.